Perspectives on Non-BLT Humanized Mouse Models for Studying HIV Pathogenesis and Therapy - Terahara, Kazutaka; Iwabuchi, Ryutaro; Tsunetsugu-Yokota, Yasuko (Viruses, 2021)
A variety of humanized mice, which are reconstituted only with human hematopoietic stem cells (HSC) or with fetal thymus and HSCs, have been developed and widely utilized as in vivo animal models of HIV-1 infection. The models represent some aspects of HIV-mediated pathogenesis in humans and are useful for the evaluation of therapeutic regimens. However, there are several limitations in these models, including their incomplete immune responses and poor distribution of human cells to the secondary lymphoid tissues. These limitations are common in many humanized mouse models and are critical issues that need to be addressed. As distinct defects exist in each model, we need to be cautious about the experimental design and interpretation of the outcomes obtained using humanized mice. Considering this point, we mainly characterize the current conventional humanized mouse reconstituted only with HSCs and describe past achievements in this area, as well as the potential contributions of the humanized mouse models for the study of HIV pathogenesis and therapy. We also discuss the use of various technologies to solve the current problems. Humanized mice will contribute not only to the pre-clinical evaluation of anti-HIV regimens, but also to a deeper understanding of basic aspects of HIV biology.